Quality education for sustainable development in Nigeria: the role of multidisciplinary approach to collaborative research in school librarianship (2017)
A strong correlation exists between education and sustainable development. In the light of this fact, material, human and financial resources have been committed to education by the three tiers of government in Nigeria. Despite this, there is still public outcry against the continual falling Standard of education in Nigeria. In an attempt to solve this problem, individuals and different groups of experts from the same disciplines have been conducting researches without collaborating with researchers from other disciplines. However, it is evident that the educational problem of mass failure of students in public examinations is yet to be solved. This paper therefore proposes a new paradigm of collaborative multidisciplinary research approach which will bring together practitioners and teams of experts from many disciplines in the field of education. This study posits that the outcome of such collaborative approach would include Provision of new Solutions to the problem; new discoveries in the areas of methods of teaching; better techniques in curriculum delivery; strategies for improved reading culture of students; Provision of efficient library Services and advancement of knowledge.